2020
DOI: 10.1212/wnl.0000000000009577
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal neurofilament light

Abstract: ObjectiveTo measure exosomal and plasma levels of candidate blood biomarkers in veterans with history of mild traumatic brain injury (mTBI) and test their relationship with chronic symptoms.MethodsExosomal and plasma levels of neurofilament light (NfL) chain, tumor necrosis factor (TNF)–α, interleukin (IL)–6, IL-10, and vascular endothelial growth factor (VEGF) were measured using an ultrasensitive assay in a cohort of 195 veterans, enrolled in the Chronic Effects of Neurotrauma Consortium Longitudinal Study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 42 publications
5
63
0
Order By: Relevance
“…The finding of chronic elevations of EV GFAP and NfL at 1 year postinjury in patients with moderate or severe TBIs expands on our previous work in which EV and plasma NfL levels were elevated many years after injury in military personnel with repetitive mTBI 9 . Our finding that EV GFAP and NfL continue to have diagnostic and prognostic utility when sampled at 1 year postinjury constitute increasing evidence that GFAP and NfL are valuable chronic biomarkers of TBI.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The finding of chronic elevations of EV GFAP and NfL at 1 year postinjury in patients with moderate or severe TBIs expands on our previous work in which EV and plasma NfL levels were elevated many years after injury in military personnel with repetitive mTBI 9 . Our finding that EV GFAP and NfL continue to have diagnostic and prognostic utility when sampled at 1 year postinjury constitute increasing evidence that GFAP and NfL are valuable chronic biomarkers of TBI.…”
Section: Discussionsupporting
confidence: 79%
“…Our lab has recently investigated the utility of EV biomarkers in a sample of military personnel and Veterans with remote mTBI. Our findings suggest that repetitive, remote mTBIs are associated with elevations of EV NfL, especially among individuals with chronic neurobehavioral or psychological symptoms 9 . However, the utility of EV NfL in civilian patients with a history of single TBI and in comparison with EV GFAP has not been previously investigated.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…An important area of brain injury and disease research is the search for blood biomarkers that reflect brain processes, to predict disease course and used as readouts to assess utility of interventions to improve outcome for patients. Recently, a range of proteins, including neurofilament light (NfL) polypeptide released from damaged axons, have been proposed as viable biomarkers of mild TBI ( 60 , 124 , 125 ). The brain's immune response to mild TBI is also evident in the blood, as elevated c-reactive protein (CRP) levels at admission are independently associated with the increased risk of persistent psychological problems and cognitive impairment ( 29 ).…”
Section: The Immune Response To Mild Tbimentioning
confidence: 99%
“…This correlation was not present when measuring total Tau in plasma, although this measure was positively associated with cumulative head impact index ( Alosco et al, 2018 ). Guedes et al (2020) measured plasma and exosomal levels of NF-light in veterans with history of mTBIs and found that those experiencing chronic PCS and post-traumatic stress disorder (PTSD) exhibited the highest NF-light levels both in plasma and exosomes.…”
Section: Biomarkers In Mtbimentioning
confidence: 99%